4(x+6)-2x=x+15

Simple and best practice solution for 4(x+6)-2x=x+15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+6)-2x=x+15 equation:


Simplifying
4(x + 6) + -2x = x + 15

Reorder the terms:
4(6 + x) + -2x = x + 15
(6 * 4 + x * 4) + -2x = x + 15
(24 + 4x) + -2x = x + 15

Combine like terms: 4x + -2x = 2x
24 + 2x = x + 15

Reorder the terms:
24 + 2x = 15 + x

Solving
24 + 2x = 15 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
24 + 2x + -1x = 15 + x + -1x

Combine like terms: 2x + -1x = 1x
24 + 1x = 15 + x + -1x

Combine like terms: x + -1x = 0
24 + 1x = 15 + 0
24 + 1x = 15

Add '-24' to each side of the equation.
24 + -24 + 1x = 15 + -24

Combine like terms: 24 + -24 = 0
0 + 1x = 15 + -24
1x = 15 + -24

Combine like terms: 15 + -24 = -9
1x = -9

Divide each side by '1'.
x = -9

Simplifying
x = -9

See similar equations:

| 10=3(-x+4) | | b-8+4b=28 | | 553= | | 8(6n+1)+4n=424 | | 0.10(14-x)+x=0.40(14) | | -16=-8+r | | 96n=18*8 | | -(p+8)=10+2p | | 8y-11y=27 | | 3(x+6)=3(x+11) | | -2(-9w+4)-8w=2(w-8)-4 | | 5x+26=7(6+x)+2x | | 9c=180*5 | | 7x+34=10x-11 | | 5x+9-6x=8-12 | | 6(x+3)=6(x+10) | | 5(5m+7)=-115 | | 28x+2y=12.4 | | 6x-3=6x-3 | | 17y-8y=5 | | -28=x+17 | | x+-12=13 | | -2x+23=-(8x-5) | | 6x+15=-2x-17 | | -6(x-2)=3x+48 | | 5x+8+6x=8x+9 | | 84=-20x | | x+-12=12 | | 2x+15=-3x-18 | | 2x+15=2x-18 | | 2lnx-3lny=-5 | | -8(v+5)-4v=24+4v |

Equations solver categories